Structural and Functional Characterizations of Al+ Implanted 4H-SiC Layers and Al+ Implanted 4H-SiC p-n Junctions after 1950°C Post Implantation Annealing. (1st January 2016) - Nipoti, Roberta; Parisini, Antonella; Sozzi, Giovanna; Puzzanghera, Maurizio; Parisini, Andrea; Carnera, Alberto
Abstract : In the case of Al + implanted 4H-SiC, a post implantation annealing temperature of 1950°C has the beneficial effect of maximizing both the electrical activation of implanted Al and the reordering of the lattice damaged by the Al ions. However, the formation of extended defects in the implanted layers and that of carbon vacancies in the n-type epi-layers below the implanted layers may be hardly avoided. This study contains the results of structural and electrical investigation showing that: (i) on increasing the implanted Al concentration different type of extended defects form and grow; (ii) a strong anisotropic hole transport occurs when the Al implanted surface layer is confined by and contains stacking faults. This study also reports experimental and simulated values of the area and the perimeter components of the current density of Al + implanted 4H-SiC p-i-n diodes. The simulations show that these components may be, at least qualitatively, accounted for by the sole hypothesis of carrier lifetime dominated by carbon-vacancy related traps and by the presence of a negative fixed charge at the sample surface.